Visual impairment and all-cause mortality: a real-world retrospective cohort study - Fu, Chenxi; Gu, Qinyi; Li, Xi; Wang, Zhouqian; Zhang, Xiaoyu; Chen, Wei (Frontiers in Public Health, 2025)
BackgroundVI (visual impairment) significantly impacts global public health, and there are few studies and inconsistent results on the impact of VI on mortality in Chinese adults. Our study aims to investigate the association between VI and the all-cause mortality risk in Chinese adults and to explore potential sex differences.MethodsThis retrospective cohort (from July 17, 2010 to September 30, 2021) utilized data from the Yinzhou Health Information System, involving 182,468 individuals with valid visual acuity (VA) examination records. We assessed VI, defined as a presenting VA of the better eye worse than 0.5, using two variables: a binary variable (non-VI vs. VI) and a categorical variable (non-VI: VA ≥ 0.5; mild VI: 0.3 ≤ VA < 0.5; moderate VI: 0.1 ≤ VA < 0.3; severe VI: VA < 0.1). Cox proportional hazards multivariable regression models were used to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs) for the all-cause mortality risk. Subgroup analyses were also conducted based on sex and age.ResultsDuring a median follow-up of 3.87 years, there were 2,632 death events, with 1,579 occurring in the non-visual impairment (VI) group and 1,053 in the VI group. Individuals with VI (VA < 0.5) had an increased all-cause mortality risk (HR, 1.15; 95% CI, 1.06–1.24), and this association persisted in old adults (HR, 1.15; 95% CI, 1.06–1.25). Old females with moderate or severe VI showed significantly higher all-cause mortality risks, with HRs of 1.32 (95% CI, 1.13–1.55) and 2.16 (95% CI, 1.35–3.46), respectively. Among old male participants, the increased all-cause mortality risk was only observed in those with moderate VI (HR, 1.42; 95% CI, 1.23–1.65).ConclusionVI was associated with an increased all-cause mortality risk in Chinese old population. Sex differences were also observed in the associations between the VI level and the all-cause mortality risk.